Endoscopic Decompression of the Labyrinthine Segment of the Facial Nerve. Issue 10 (December 2020) - Cornu, Nicolas; Marchioni, Daniele; Eliezer, Michael; Verillaud, Benjamin; Hautefort, Charlotte; Green, Andrew; Marc, Morgane; Bresson, Damien; Froelich, Sebastien; Herman, Philippe; Kania, Romain
Abstract : Objective: To describe the outcome and feasibility of an exclusive endoscopic transcanal transpromontorial approach (ETTA) for decompression of the labyrinthine segment of the facial nerve (LSFN). Patient: A 60-year-old man with a left-sided transverse fracture of temporal bone involving the LSFN, resulting in a grade VI House–Brackmann (HB) facial palsy, associated with ipsilateral total sensorineural hearing loss. Intervention: Surgical decompression of the LSFN by ETTA. Main Outcome Measure: The patient underwent ETTA which allowed complete exposure and decompression of the LSFN. Results: One year postoperatively, the patient had recovered with House–Brackmann grade II facial function. Conclusion: ETTA can be considered a valuable and appropriate technique for posttraumatic decompression of LSFN, associated with unilateral total sensorineural hearing loss. The procedure resulted in significant facial nerve function improvement. ETTA should be considered both a scarless, mastoid conserving and less invasive surgical technique for posttraumatic LSFN decompression associated with pre-existing cochlear impairment.